소장 병변 진단에서 이중풍선소장내시경과 소장조영술의 비교 - 조지윤; Ji Yun Jo; 변정식; Jeong Sik Byeon; 최기돈; Kee Don Choi; 박혜원; Hye Won Park; 이진혁; Gin Hyug Lee; 명승재; Seung Jae Myung; et al. (The Korean journal of gastroenterology, 2006)
목적: 소장 질환의 진단과 치료에서 이중풍선소장내시경의 역할은 아직 정립되어 있지 않다. 이번 연구에서는 소장질환이 의심되는 환자에서 소장조영술과 이중풍선소장내시경의 진단 가치를 비교 분석해 보고자 하였다. 대상 및 방법: 2005년 1월부터 2005년 5월까지 소장 병변이 의심되는 환자들을 대상으로 하였다. 연구에 포함된 환자들에 대해 이중풍선소장내시경과 소장조영술을 모두 시행하였고 그 결과를 비교하였다. 결과: 모두 18명(남:여=12:6, 14-82세)의 환자가 포함되었다. 이중풍선소장내시경과 소장조영술을 시행한 적응증은 원인 불명 위장관 출혈 10예, 원인 불명 복부 통증 5예, 만성 설사 2예, 복부 전산화단층촬영에서 소장벽 비후가 있었던 1예였다. 원인 불명 위장관 출혈 10예 중 소장조영술에서 정상이었던 4예에서 이중풍선소장내시경을 통해 궤양이나 미란과 같은 의미 있는 병변을 찾을 수 있었다. 나머지 6예는 두 검사에서 진단의 차이가 없었다. 원인 불명 복통이 있었던 5예 중 3예는 림프종, 공장 협착, 베체트 병으로 두 검사에서 같은 진단을 내릴 수 있었다. 한편, 2예에서는 서로 다른 소견을 보였는데, 소장조영술에서 크론병을 의심하였던 1예는 이중풍선소장내시경에서 정상으로 확인하였고, 소장조영술에서 악성 병변으로 생각하였던 1예는 이중풍선소장내시경에서 원인 미상의 만성 양성 궤양으로 추정되었으나 확진하지는 못했다. 만성 설사가 있었던 2예 중 1예는 두 검사에서 모두 크론병으로 진단하였고, 나머지 1예는 소장조영술에서 장결핵이 의심되었으나 이중풍선소장내시경을 통해 림프관확장증으로 확진하였다. 복부 전산화단층촬영에서 이상 소견을 보였던 1예는 두 검사 모두 정상이었다. 결론: 이중풍선소장내시경은 소장 질환의 진단에서 소장조영술보다 우수하였으며 향후 소장 질환의 진단과 치료에 중요한 역할을 담당할 것으로 생각한다. Background/Aims: The role of double balloon enteroscopy (DBE) is still evolving. The aim of this study was to compare the diagnostic yield of DBE with that of small bowel series (SBS). Methods: We enrolled patients with suspected small bowel disease consecutively, and performed both DBE and SBS in all patients. Results: Eighteen patients (M:F=12:6, 14-82 years) were included. Indications for small bowel evaluation were obscure gastrointestinal bleeding (10), abdominal pain (5), diarrhea (2) and abnormal CT finding (1). Of 10 obscure gastrointestinal bleeding patients, 6 showed the same findings in both studies. However, 4 showed negative findings in SBS while DBE detected erosions or ulcerations. Of 5 abdominal pain patients, 3 showed the same results in both studies. However, 2 demonstrated different results. One was suspected of early Crohn`s disease in SBS, but proved to be normal in DBE, and the other was suspected of malignancy in SBS but was suspected of benign ulcers in DBE. Of 2 chronic diarrhea patients, one was diagnosed as Crohn`s disease in both studies. The other was suspected of tuberculosis in SBS but diagnosed as lymphangiectasia by DBE with biopsy. One patient with jejunal wall thickening in CT proved to be normal in both DBE and SBS. There were no serious complications associated with DBE and SBS. Conclusions: DBE is better than SBS in terms of diagnostic accuracy. DBE may become an important method for the evaluation of small bowel diseases. (Korean J Gastroenterol 2006;48:25-31)